Effect of UV-Treatment on the Wettability of Polycarbonate - Subedi, D. P.; Tyata, R.B.; Rimal, D. (Kathmandu University Journal of Science, Engineering and Technology, 2009)
This paper presents the results of the effect of ultra-violet (UV) radiation treatment on the wettability of polycarbonate surfaces. Two wavelengths of UV radiation, namely 254 nm and 365 nm, were employed in the study. The impact of treatment duration on sample wettability was assessed by measuring contact angles with two different test liquids. The investigation revealed that treatment with shorter wavelength UV radiation resulted in higher wettability compared to treatment with longer wavelength radiation. Furthermore, the total surface free energy of the sample, calculated using a two-liquid model, showed an increase of approximately 7 mJ/m² from the original value of 30 mJ/m² after 25 minutes of treatment with UV radiation at 254 nm.